Women’s perceptions and experiences of the challenges in the process of male infertility treatment: A qualitative study - Taghipour, Ali (Electron Physician, 2017)
BACKGROUND: Despite the fact that both men and women are equally subject to infertility, it is usually women who bear the burden of treatment and its consequences, even in cases of male infertility. Therefore, it is more necessary to recognize their health problems in order to help them. AIM: To explore women’s perceptions and experiences of the challenges they face in the process of male infertility treatment. METHODS: This qualitative study was conducted during 2014–2015 using content analysis. Thirty semi-structured interviews were conducted with women whose husbands suffered from male infertility. Purposive sampling was conducted until data saturation was achieved. All interviews were recorded, transcribed and analyzed using conventional content analysis adopted by Graneheim and Lundman. RESULTS: From data analysis, the major category of “treatment-related stresses” and four subcategories of “high treatment expenses”, “inefficiency of healthcare system”, “being captive in the infertility treatment” and “treatment failure” emerged. CONCLUSION: Experiences of women who face male infertility indicate their various concerns in the process of treatment. Therefore, it is required to develop emotional and financial support for the clients and to promote their quality of healthcare services. In addition, awareness of treatment challenges of these women can assist proper planning to promote the quality of services they need.